The follicular-phase depot GnRH agonist protocol results in a higher live birth rate without discernible differences in luteal function and child health versus the daily mid-luteal GnRH agonist protocol: a single-centre, retrospective, propensity score matched cohort study - Ying Zhang; Wenxian Zhao; Yifan Han; Xin Chen; Shaoyuan Xu; Yueyue Hu; Honglu Diao; Changjun Zhang (BMC, 2022)
Abstract Background The gonadotropin-releasing hormone agonist (GnRH-a) has been used in in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles for a long time. This paper evaluates the efficacy and safety of two commonly used protocols (follicular-phase depot GnRH-a protocol and daily mid-luteal long GnRH-a protocol) in normal responders undergoing IVF/ICSI using propensity score matching (PSM) analysis. Methods A total of 6,816 infertile women treated within the period from January 2016 to September 2020 were stratified into cohorts. A total of 2,851 patients received the long-acting group (depot GnRH-a protocol), and 1,193 used the short-acting group (long GnRH-a protocol) after the data-selection process. PSM was utilized for sampling by up to 1:1 nearest neighbour matching to adjust the numerical difference and balance the confounders between groups. The primary outcome was the live birth rate (LBR). Multivariable logistic analysis was used to evaluate the difference between these two protocols in relation to the LBR. Result(s) In this study, 1:1 propensity score matching was performed to create a perfect match of 964 patients in each group. After matching, the blastocyst formation rates, oestradiol (E2) value on Day hCG + 9, progesterone (P) value on Day hCG + 9, implantation rates, clinical pregnancy rates, and LBR were more favourable in the depot GnRH-a protocol than in the long GnRH-a protocol (P < 0.05). However, the moderate or severe OHSS rates were higher in the depot group than in the long group (P < 0.001). There were no significant differences in endometrial thickness, luteal support medication, early pregnancy loss rates, mid- and late-term pregnancy loss rates, or foetal malformation rates between the two protocols. Conclusion(s) Compared with the daily short-acting GnRH agonist protocol, the follicular-phase depot GnRH-a protocol might improve LBRs in normogonadotropic women without discernible differences in luteal function and child health.